Meningkatkan Hasil Belajar Lompat Jauh Melalui Modifikasi Bermain Lompat Katak (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
Classroom Action Research was conducted in order to determine the long jump increase learning outcomes through modifications play leapfrog learning penjas orchestra for elementary school fourth-grade students Bendan 01 Pekalongan. This study uses action research. The results of the study in the first cycle results in the learning activities of students have reached 73.37%, while for the second cycle has reached 87.79% with very good success qualifications. Percentage success of students in the first cycle skill aspect that is equal to 70.31% and the implementation of the second cycle increased to 89.84% with complete categories. The percentage of the aspects of the first cycle of knowledge that is equal to 74.89% and the second cycle was 83.96% with complete categories. Percentage attitude to aspects of the first cycle is equal to 77.86% and the second cycle was 87.50% with complete categories. While the determination to learn the indicators of success in 75%.